Diagnosis of Chlamydia trachomatis in patients with reactive arthritis and undifferentiated spondyloarthropathy - Kumar, Praveen; Bhakuni, Darshan Singh; Rastogi, Sangita (The Journal of Infection in Developing Countries, 2014)
Introduction: There is a paucity of information on the frequency of Chlamydia trachomatis-induced reactive arthritis (ReA) and undifferentiated spondyloarthropathy (uSpA) in India. In this study, arthritic patients suffering from ReA, uSpA, and rheumatoid arthritis (RA) were screened to investigate the presence of C. trachomatis infection in the synovial fluid (SF) or serum by molecular and non-molecular methods. Methodology: A total of 76 arthritic patients with ReA (n = 16) and uSpA (n = 22) composed the study group while those with RA (n = 38) served as controls. The detection of C. trachomatis DNA was done by semi-nested PCR (snPCR) and nested PCR (nPCR) targeting two different genes of C. trachomatis, namely major outer membrane protein and plasmid, respectively. The presence of serum or SF immunoglobulin IgG and IgA antibodies against C. trachomatis was studied by commercial enzyme-linked immunosorbent assay kits. Results: The SF from 9 of 38 (23.6%) patients (5 with ReA and 4 with uSpA) was positive for at least one C. trachomatis DNA by snPCR or nPCR in comparison to RA (1/38 [2.6%]; p value < 0.05). There was no correlation between the snPCR or nPCR and the serological results of patients with ReA or uSpA. Conclusions: As molecular diagnostic techniques established intra-articular C. trachomatis infection among this group of seronegative spondyloarthropathies in India, these findings should be viewed with concern, and snPCR or nPCR should be considered for a more reliable diagnosis.